Ultrasound Molecular Imaging of Lymphocyte-endothelium Adhesion Cascade in Acute Cellular Rejection of Cardiac Allografts. Issue 8 (August 2019) - Xie, Yu; Chen, Yihan; Zhang, Li; Wu, Meiying; Deng, Zhiting; Yang, Yali; Wang, Jing; Lv, Qing; Zheng, Hairong; Xie, Mingxing; Yan, Fei
Abstract : Background: Acute cellular rejection is one of the main reasons for graft failure after heart transplantation. A precise diagnosis at the early stage of acute cellular rejection is a big challenge for clinicians. Given the importance of the interaction between T cells and graft endothelia in initiating rejection, we developed T cell-microbubble complexes (cell-MBs) as ultrasound molecular imaging probes to monitor the lymphocyte–endothelium adhesion cascade in cardiac acute cellular rejection. Methods: Cell-MBs were fabricated by incubating lymphocytes with anti-CD4 antibody-conjugated MBs (MBCD4 ). The potential of cell-MBs as probes for detecting acute cardiac rejection was examined. Donor hearts from Brown Norway or Lewis rats were transplanted into Lewis recipients. Ultrasound molecular imaging was performed on allografts of untreated or cyclosporin A (CsA)-treated recipients, and isografts on posttransplantation day 3. Histology was used to assess rejection grades. Results: We detected a significantly stronger ultrasound molecular imaging signal of cell-MBs than that of MBCD4 or plain MBs in allografts of untreated and CsA-treated recipients. No signal enhancement was observed in isografts with cell-MBs. The signal of cell-MBs in allografts of the untreated group was significantly higher than that in the CsA-treated group, and the signal in the CsA-treated group was higher than that in isografts. Histology confirmed grade 3R rejection in the untreated group, grade 2R rejection in CsA-treated group, and no rejection in isografts. Conclusions: Our study suggests that cell-MBs can function as a promising probe to image the dynamic lymphocyte–endothelium adhesion cascade for noninvasive diagnosis of cardiac acute cellular rejection. Abstract : Supplemental Digital Content is available in the text.